Malignant mixed mullerian tumour of the endometrium with a synchronous ovarian cancer- a rare association - Chennaihgari, Sathyavani; Pidaparthy, Padmaja; Samal, Rajnish; Arun Kumar, Nalini; Kumari, Agitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Synchronous malignancies of genital tract are extremely uncommon especially those with independent histopathologies. We are reporting a rare case with a unique presentation. A 79 year old nulliparous lady presented with foul smelling discharge and bleeding per vaginum. Examination revealed an abdominopelvic mass and a friable polypoidal growth projecting from the cervical os. Biopsy of the polyp indicated mixed malignant mullerian tumour. CT scan revealed a large ovarian tumour with solid and cystic areas indicating ovarian malignancy. During laparotomy patient was also found to have chronic inversion of uterus secondary to the polypoidal growth protruding from the cervix. Histopathology confirmed mixed malignant mullerian tumour of the endometrium and serous cyst adenocarcinoma of the right ovary.